The Best Method for Memorizing the Al-Qur'an that Supports the Quality of Students at SDIT Insan Teladan - Reza Fauzi Rasyad; Tarsono (al-Afkar, Journal For Islamic Studies, 2024)
The Qur'an, which has differentiating, warning and medicinal functions, is a guide and guidance for mankind. Muslims are obliged to maintain and protect it by always reading, writing and even trying to memorize it, therefore the superior Tahfdz Al-Qur'an program has been realized by many Integrated Islamic-based educational institutions, one of which is SDIT Insan Teladan. The guidance for tahfidz Al-Qur'an is carried out using the Wafa method which is also supported by students' motivational factors towards memorizing. Based on research results, this method is considered very effective in the process of memorizing the Al-Quran because in practice it is easy, fast and fun, allowing children to enjoy every memorization process. Apart from that, the wafa method also supports the quality of students' memorization as proven by several championships that SDIT Insan Teladan students have obtained in the fields of tahfdz and religion.